Copper material with surface molecular passivation layer and preparation method and application thereof
By forming a nano-scale molecular passivation layer on the surface of the copper material, using strong interfacial binding force and quinone-type structure organic ligands, the problem of low durability caused by the oxidation of copper materials is solved, and a wider application in the high-tech field is achieved.
Patent Information
- Application Number
- CN202510113543.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
AI Technical Summary
Copper materials have low durability due to their oxidation, which affects their application in high-tech fields, especially in semiconductor electronics and flexible electronic technologies.
Using organic ligands with strong interfacial binding force and quinone structure, such as TAC, TPA-Ca, NPC-Ca and TNC, a nanoscale molecular passivation layer is formed by reacting with the surface of the copper material.
It realizes that while maintaining the physical properties of copper materials, it effectively prevents oxidation and improves its durability and environmental adaptability in various extreme environments.
Smart Images

Figure CN119900022A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal protective materials, and in particular relates to a copper material with a surface molecular passivation layer and a preparation method and application thereof. Background Art
[0002] Copper materials have become one of the most widely used non-precious metals in modern industry and electronic information fields due to their excellent electrical conductivity, thermal conductivity and easy processing. However, the easy oxidation of copper seriously restricts the durability of its excellent physical properties, which not only leads to huge economic losses, but also limits its wide application in high-tech fields. Especially in semiconductor electronics, the oxidation of copper materials as wires will seriously affect the electrical and thermal conductivity of the device, and may even cause circuit failures or catastrophic accidents. In the face of the development of the next generation of flexible electronic technology, although copper-based conductive inks / pastes have economic cost advantages, they have poor stability and are difficult to compete with materials such as gold, silver and liquid metals.
[0003] In the past few decades, copper anti-oxidation technology has made significant progress. However, how to keep the copper surface passivated without damaging its inherent physical properties remains a daunting challenge. Classic copper anti-corrosion strategies include coatings, molecular inhibitors, and molecular passivation layers. Coating anti-corrosion strategies usually require thicker physical barriers to resist environmental erosion, but this will greatly reduce the thermal and electrical conductivity of the copper material itself. The molecular inhibitor strategy is to dissolve an appropriate amount of inhibitor in a corrosive liquid medium to hinder the oxidation reaction of the copper material, which is usually used for industrial copper corrosion protection. The molecular passivation strategy is to adsorb antioxidant molecules on the copper surface to enhance its environmental adaptability with minimal damage to the physical properties of the material itself. However, due to limited antioxidant capacity and complex passivation processes (such as solvothermal, vapor deposition, and electrochemical deposition), molecular passivation technology faces great challenges in industrial mass production.
[0004] For the next generation of high-density integrated semiconductor industry, flexible electronics and optoelectronics, it is of great strategic significance to develop simple, robust, durable and highly environmentally adaptable copper anti-oxidation strategies. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a copper material with a surface molecular passivation layer.
[0006] Another object of the present invention is to provide a method for preparing the copper material.
[0007] Another object of the present invention is to provide the use of specific organic ligands in preparing a molecular passivation layer on the surface of a copper material.
[0008] The technical solution of the present invention is as follows:
[0009] A copper material having a surface molecular passivation layer, wherein the organic ligand forming the surface molecular passivation layer is selected from TAC, TPA-AC, NPC-AC, TNC-AC, TPA-Ca, NPC-Ca, TNC, TPATC, TPAS-Ca, TPAS-Ca, TPA-TA, NPC-TA, TPAS-TA and TPADC (the specific structure is as follows Figure 1 shown).
[0010] In a preferred embodiment of the present invention, the organic ligand is selected from TAC, TPA-Ca, NPC-Ca and TNC.
[0011] In a preferred embodiment of the present invention, the copper material is selected from pure copper, copper alloy, copper powder, copper ink and copper paste.
[0012] The method for preparing the copper material with a surface molecular passivation layer comprises placing the copper material without a surface oxide layer in an organic solvent solution of the organic ligand at room temperature for reaction, and then removing excess organic ligands.
[0013] In a preferred embodiment of the present invention, the organic solvent is selected from methanol, ethanol and dichloromethane.
[0014] More preferably, the reaction time is 5-8 hours.
[0015] The use of an organic ligand in preparing a molecular passivation layer on the surface of a copper material, wherein the organic ligand is selected from TAC, TPA-AC, NPC-AC, TNC-AC, TPA-Ca, NPC-Ca, TNC, TPATC, TPAS-Ca, TPAS-Ca, TPA-TA, NPC-TA, TPAS-TA and TPADC.
[0016] In a preferred embodiment of the present invention, the organic ligand is selected from TAC, TPA-Ca, NPC-Ca and TNC.
[0017] In a preferred embodiment of the present invention, the copper material is selected from pure copper, copper alloy, copper powder, copper ink and copper paste.
[0018] The beneficial effects of the present invention are: (1)
[0019] 1. Existing mass-produced anti-corrosion technologies are difficult to balance in inhibiting surface oxidation and maintaining intrinsic performance. The present invention is based on the extremely strong interfacial bonding force of catechol and its variants and the cation-π interaction between the quinone structure and the aromatic amine free radical cation to form a nano-scale molecular passivation layer on the substrate surface, which can balance the anti-corrosion effect and intrinsic physical properties (electrical and thermal conductivity);
[0020] 2. The preparation of the surface molecular passivation layer in the present invention is simple, has low requirements on equipment and environment, and has low economic cost, and can break the technical barriers for the preparation of high-quality nanoscale passivation layers (such as electrochemical polymerization; physical vapor deposition, etc.);
[0021] 3. The present invention has excellent environmental adaptability and can withstand a variety of corrosive extreme environments (high temperature, high humidity, strong alkali and strong ultraviolet light) for a long time;
[0022] 4. The preparation method of the present invention is universal and is not only applicable to pure copper, but can also be extended to copper alloys (brass and bronze), copper powder, copper ink and copper slurry, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is the chemical structural formula of the organic ligand involved in the present invention that can be assembled on the surface of the copper material to form a high-efficiency passivation layer.
[0024] Figure 2 This is a high-resolution transmission electron microscope (HR-TEM) of the cross section of Cu-TAC prepared in Example 5 of the present invention, and the inset is the electron diffraction pattern of the sample.
[0025] Figure 3 The optical photograph, microscopic optical photograph and scanning electron microscope image (from left to right at a time) of the Cu-TAC prepared in Example 5 of the present invention.
[0026] Figure 4 (A) Raman spectra and X-ray diffraction spectra (XRD) of the Cu-TAC prepared in Example 5 of the present invention before and after being immersed in a 0.1M NaOH aqueous solution for different time periods.
[0027] Figure 5 (A) The electrical conductivity of Cu-TAC prepared in Example 5 of the present invention before and after being immersed in a 0.1M NaOH aqueous solution for different time periods; (B) The thermal conductivity of Cu-TAC after being immersed in a 0.1M NaOH aqueous solution for one day.
[0028] Figure 6 (A) Raman spectra and (B) X-ray diffraction spectra (XRD) of the Cu-p-TAC prepared in Example 7 of the present invention before and after being immersed in a 0.1M NaOH aqueous solution for different time periods.
[0029] Figure 7 The conductivity change of the Cu-p-TAC prepared in Example 7 of the present invention before and after being immersed in a 0.1M NaOH aqueous solution for one month is shown. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0031] Example 1
[0032] Dissolve tris(4-aminophenyl)amine (14.5 mg, 0.05 mmol) and 3,4-dihydroxybenzaldehyde (20.7 mg, 0.15 mmol) in 5 mL of methanol, add a drop of acetic acid, stir at room temperature in the dark for 15 h, concentrate, wash with methanol several times and dry to obtain 4,4',4"-((1E,1'E,1"E)-((nitrotri(benzene-4,1-diyl))tris(iminomethylene))tris(methylene))tris(benzene-1,2-diphenol) powder (TAC, structural formula: Figure 1 shown).
[0033] Example 2
[0034] 4-aminotriphenylamine (500 mg, 1,54 mmol), 3,4-dimethoxyphenylboronic acid pinacol ester (610 mg, 2.30 mmol), Pd[P(C6H5)3]4 (46.2 mg, 0.04 mmol) and K2CO3 (2.0 mL, 2MH2O) were added to 30 mL of anhydrous tetrahydrofuran. The above mixture was heated to 70 ° C under a nitrogen atmosphere and stirred overnight. After the reaction was completed, the reaction system was cooled to room temperature, and the crude product was extracted with dichloromethane several times, washed with brine several times and dried over anhydrous magnesium sulfate, and then purified by column chromatography to obtain a white solid, which was the intermediate product 3',4'-dimethoxy-N,N-diphenyl-[1,1'-biphenyl]-4-amine.
[0035] 1 H NMR(500MHz, CDCl3)δ7.43(d,J=8.5Hz,2H),7.28-7.23(m,4H),7.12(d,J=8.0Hz, 6H),7.08(s,1H),7.02(t,J=7.2Hz,2H),6.92(d,J=8.3Hz,2H),3.92-3.81(m,6H). 13 CNMR(500MHz,CDCl3)δ149.17,148.39,147.73,146.79,133.81,129.26,127.50,12 6.86,124.29,124.18,122.84,118.97,111.55,110.15,77.29,77.04,76.79,55.98.
[0036] Add 20 mL of anhydrous dichloromethane and 3',4'-dimethoxy-N,N-diphenyl-[1,1'-biphenyl]-4-amine (300 mg, 0.79 mmol) to a dry Schlenk tube, then cool to -20°C, stir vigorously and add BBr3 (1.5 mL, 2M dichloromethane) dropwise. After the reaction is carried out at room temperature for 12 hours, water is added to quench the reaction, and the reaction mixture is poured into 80 mL of an ice-water mixture, followed by suction filtration. The resulting solid is washed with dichloromethane and ethanol several times and then dried to obtain a yellow powder, which is the final product 4'-(diphenylamino)-[1,1'-biphenyl]-3,4-diphenol (TPA-Ca, with a structural formula as shown below): Figure 1 shown).
[0037] The characterization data of TPA-Ca are: 1 H NMR(500MHz,DMSO-d6)δ8.96(br,2H),7.22(t,J=7.6Hz,6H),6.95-6.88(m,8H), 6.70(dd,J=8.3,4.3Hz,1H), 6.50(d,J=2.4Hz,1H), 6.38(dd,J=8.3,2.3Hz,1H). 13 C NMR (126MHz, DMSO) δ148.25,146.50,143.12,139.04,129.61,122.50,121.91,117.77,116.60,114.51.HRMS for TPA-Ca:C 24 H 19 NO2m / z:[M-H] - Calc.352.1416; Found 352.1349.
[0038] Example 3
[0039] N-(4-bromophenyl)carbazole (500 mg, 1,55 mmol), 3,4-dimethoxyphenylboronic acid pinacol ester (614 mg, 2.33 mmol), Pd[P(C6H5)3]4 (46.2 mg, 0.04 mmol) and K2CO3 (2.0 mL, 2MH2O) were added to 30 mL of anhydrous tetrahydrofuran. The above mixture was heated to 70 ° C under a nitrogen atmosphere and stirred overnight. After the reaction was completed, the reaction system was cooled to room temperature, and the crude product was extracted with dichloromethane several times, washed with brine several times and dried over anhydrous magnesium sulfate, and then purified by column chromatography to obtain a white solid, which was the intermediate product 9-(3',4'-dimethoxy-[1,1'-biphenyl]-4-yl)-9H-carbazole.
[0040] 1H NMR(500MHz, CDCl3)δ8.15(d,7.7Hz,2H),7.77(d,J=8.3Hz,2H),7.61(d,J=8.3Hz,2H),7.49-7.38(m,4H), 7.28(dd,J=15.6,8.4Hz,2H),7.26-7.22(m,1H),7.20(s,1H),6.99(d,J=8.2Hz,1H),3.95(d,J=20.1Hz,6H) 13 C NMR (126MHz, CDCl3) δ149.36,148.99,140.93,140.20,136.45,133.30,128.19,127.36 ,125.97,123.43,120.35,119.53,111.66,110.46,109.84,77.30,77.05,76.80,56.05.
[0041] Add 20 mL of anhydrous dichloromethane and 9-(3',4'-dimethoxy-[1,1'-biphenyl]-4-yl)-9H-carbazole (300 mg, 0.79 mmol) to a dry Schlenk tube, then cool to -20°C, stir vigorously and add BBr3 (1.5 mL, 2M dichloromethane) dropwise. After the reaction is carried out at room temperature for 12 hours, water is added to quench the reaction, and the reaction mixture is poured into 80 mL of an ice-water mixture. The solid is filtered, washed with dichloromethane and ethanol several times, and then dried to obtain a light green powder, which is the final product 4'-(9H-carbazole-9-yl)-[1,1'-biphenyl]-3,4-diphenol (NPC-Ca, with a structural formula as shown in FIG. Figure 1 shown).
[0042] The characterization data of NPC-Ca are: 1 H NMR(500MHz,DMSO-d6)δ9.78-8.62(br,2H),8.32(d,J=7.6Hz,2H),7.90(m,2H),7.75-7.6 4(m,2H),7.5(s,4H),7.36(s,2H),7.23(s,1H),7.17-7.04(m,1H),6.94(d,J=8.0Hz,1H). 13 C NMR (126MHz, DMSO) δ146.23,146.03,140.59,140.22,140.15,135.55,131.05,127. 86,127.41,126.71,123.20,120.99,120.60,118.27,116.64,114.45,110.18.HRMS for NPC-Ca:C 24H 17 NO2,m / z:[M-H] - Calc.350.1259,Found350.1187.
[0043] Example 4
[0044] 3,6-dibromo-9-(4-bromophenyl)carbazole (500 mg, 1,04 mmol), 3,4-dimethoxyphenylboronic acid pinacol ester (1.238 mg, 4.70 mmol), Pd[P(C6H5)3]4 (46.2 mg, 0.04 mmol) and K2CO3 (2.0 mL, 2M H2O) were added to 30 mL of anhydrous tetrahydrofuran. The above mixture was heated to 70 ° C under a nitrogen atmosphere and stirred overnight. After the reaction was completed, the reaction system was cooled to room temperature, and the crude product was extracted with dichloromethane several times, washed with brine several times and dried over anhydrous magnesium sulfate, and then purified by column chromatography to obtain a white solid, which was the intermediate product 9-(3',4'-dimethoxy-[1,1'-biphenyl]-4-yl)-3,6-bis(3,4-dimethoxyphenyl)-9H-carbazole.
[0045] 1 H NMR (500MHz, DMSO-d6) δ8.68(s,2H),7.96(d,J=8.4Hz,2H),7.75(dd,J=8.6,1.2Hz,2H),7.70(d,J=8.3Hz,2H),7.48(d,J=8.5H z,2H),7.38(dd,J=6.6,1.6Hz,3H),7.32(d,J=8.3Hz,3H),7.08(t,J=8.2Hz,3H),3.91(d,J=3.9Hz,9H),3.82(d,J=6.3Hz,9H). 13 C NMR(126MHz,DMSO-d6)δ149.64,149.28,148.57,140.22,139.76,136.02,134.17,133.13,132 .44,128.47,127.18,125.68,124.14,119.41,119.02,112.77,111.22,110.99,110.52,56.12.
[0046] Add 20 mL of anhydrous dichloromethane and 9-(3',4'-dimethoxy-[1,1'-biphenyl]-4-yl)-3,6-bis(3,4-dimethoxyphenyl)-9H-carbazole (300 mg, 0.46 mmol) to a dry Schlenk tube, then cool to -20°C, stir vigorously and add BBr3 (1.5 mL, 2M dichloromethane) dropwise. After the reaction is carried out at room temperature for 12 hours, water is added to quench the reaction, and the reaction mixture is poured into 80 mL of an ice-water mixture, followed by suction filtration. The resulting solid is washed with dichloromethane and ethanol several times and then dried to obtain a dark green powder, which is the final product 4,4'-(9-(3',4'-dihydroxy-[1,1'-biphenyl]-4-yl)-9H-carbazole-3,6-diyl)bis(benzene-1,2-diphenol) (TNC, structural formula as shown in Figure 1 shown).
[0047] The characterization data of TNC are: 1 H NMR (500MHz, DMSO-d6) δ9.0 (br, 6H), 8.55 (s, 2H), 7.83 (d, J = 8.1Hz, 2H), 7.68 (d, J = 8.2Hz, 2H), 7.63 (d, J = 8. 5Hz,2H),7.47(d,J=8.5Hz,2H),7.19(d,J=10.5Hz,3H),7.09(d,J=7.9Hz,3H),6.88(dd,J=13.4,8.2Hz,3H). 13 C NMR(126MHz,DMSO-d6)δ146.23,146.10,146.03,145.00,139.93,133.43,132.86,127.99,12 7.20,125.25,124.06,118.52,118.32,118.17,116.58,114.71,114.42,110.47,99.95.HRMS forTNC:C 36 H 25 NO6m / z:[M-H] - Calc.566.1682; Found 566.1602.
[0048] The TAC, TPA-Ca, NPC-Ca and TNC obtained in the above Examples 1 to 4 can be used alone or in combination to prepare a passivation layer on the surface of a copper material. The copper material includes: pure copper, copper alloy (brass and bronze), copper powder, copper ink and copper slurry. The construction of the molecular passivation layer is further described below in conjunction with Examples 5 to 11.
[0049] Example 5
[0050] The clean copper foil after acid washing to remove the oxide layer was placed in a TAC methanol solution (1×10 -4 M) at room temperature for 5 h, and then ultrasonically cleaned in methanol for several times to remove excess TAC, thereby preparing Figures 2 to 6 The copper foil with a TAC passivation layer constructed on the surface shown is referred to as Cu-TAC.
[0051] Transmission electron microscopy (TEM) test results show that TAC can form a nanoscale passivation layer on the surface of copper materials ( Figure 2 ). From the results of optical photos, microscopic optical photos and scanning electron microscopy (TEM), it can be seen that the TAC passivation layer affects the color, gloss and microscopic morphology of the copper material. Raman spectroscopy (Raman) and X-ray diffraction (XRD) tests have detected that the TAC passivation layer has no effect on the physical properties of the main body of the copper material and can resist external corrosion for a long time ( Figure 3 ). Through the measurement of electrical conductivity and thermal conductivity, it can be seen that the electrical conductivity and thermal conductivity of the modified copper material before and after corrosion have no significant difference from the intrinsic values of the copper material ( Figure 4 ).
[0052] Example 6
[0053] The clean brass after acid washing to remove the oxide layer was placed in a methanol solution of TAC (1×10 -4 M) at room temperature for 8 h, and then ultrasonically cleaned in methanol for multiple times to remove excess TAC, thereby preparing brass with a TAC passivation layer on the surface, which is recorded as brass-TAC.
[0054] Example 7
[0055] The clean copper powder after acid washing to remove the oxide layer was placed in a methanol solution of TAC (1×10 -4 M) and stirred vigorously for 8 h, and ultrasonically cleaned in methanol for multiple times to remove excess TAC, thereby preparing Figure 6 and Figure 7 The copper powder with a TAC passivation layer constructed on the surface is shown as Cu-p-TAC.
[0056] Example 8
[0057] Fresh Cu-p-TAC was added into the PVA aqueous solution in a specific ratio and stirred at 90°C for 1 hour to obtain the copper-based printing ink Cu-p-PVA-TAC.
[0058] Example 9
[0059] The clean copper foil after acid washing to remove the oxide layer was placed in a methanol solution of TPA-Ca (1×10 -4M) at room temperature for 7 h, and then ultrasonically cleaned in methanol for multiple times to remove excess TPA-Ca, thereby preparing a copper foil with a TPA-Ca passivation layer on the surface, which is recorded as Cu-TPA-Ca.
[0060] Example 10
[0061] The clean copper foil after acid washing to remove the oxide layer was placed in the methanol solution of NPC-Ca (1×10 -3 M) at room temperature for 8 h, and then ultrasonically cleaned in methanol for multiple times to remove excess NPC-Ca, thereby preparing a copper foil with an NPC-Ca passivation layer on the surface, which is recorded as Cu-NPC-Ca.
[0062] Embodiment 11
[0063] The clean copper foil after acid washing to remove the oxide layer was placed in a mixture of methanol and dichloromethane (1×10 -5 M) at room temperature for 5 h, and then ultrasonically cleaned in methanol for multiple times to remove excess TNC, thereby preparing a copper foil with a TNC passivation layer on the surface, which is recorded as Cu-TNC.
[0064] All comparative samples in the present invention are bare copper materials without modification of molecular passivation layer.
[0065] Performance evaluation of molecular passivation layer on copper surface
[0066] The protective effect of the passivation layers formed in Examples 5 to 7 of the present invention and in Example 8 as a comparison on the copper material was compared with the anti-oxidation performance of the bare copper material, and the results were as follows:
[0067]
[0068]
[0069] The protective effect of the passivation layers formed in Examples 5, 9 to 11 of the present invention on pure copper was compared with the anti-oxidation performance of bare pure copper, and the results were as follows:
[0070]
[0071] It can be seen from the above table that the passivation layer formed by the present invention has a very strong protective effect on the copper material.
[0072] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A copper material having a surface molecular passivation layer, characterized in that: The organic ligand forming the surface molecular passivation layer is selected from TAC, TPA-AC, NPC-AC, TNC-AC, TPA-Ca, NPC-Ca, TNC, TPATC, TPAS-Ca, TPAS-Ca, TPA-TA, NPC-TA, TPAS-TA and TPADC.
2. The copper material with a surface molecular passivation layer according to claim 1, characterized in that: The organic ligand is selected from TAC, TPA-Ca, NPC-Ca and TNC.
3. The copper material with a surface molecular passivation layer according to claim 1 or 2, characterized in that: The copper material is selected from pure copper, copper alloy, copper powder, copper ink and copper paste.
4. The method for preparing a copper material having a surface molecular passivation layer according to any one of claims 1 to 3, characterized in that: The copper material without an oxide layer on the surface is placed in an organic solvent solution of the organic ligand at room temperature for reaction, and then the excess organic ligand is removed to obtain the product.
5. The preparation method according to claim 4, characterized in that: The organic solvent is selected from methanol, ethanol and dichloromethane.
6. The preparation method according to claim 5, characterized in that: The reaction time is 5-8h.
7. Use of organic ligands in preparing a molecular passivation layer on the surface of copper materials, characterized in that: The organic ligand is selected from TAC, TPA-AC, NPC-AC, TNC-AC, TPA-Ca, NPC-Ca, TNC, TPATC, TPAS-Ca, TPAS-Ca, TPA-TA, NPC-TA, TPAS-TA and TPADC.
8. The use according to claim 7, characterized in that: The organic ligand is selected from TAC, TPA-Ca, NPC-Ca and TNC.
9. The use according to claim 7 or 8, characterized in that: The copper material is selected from pure copper, copper alloy, copper powder, copper ink and copper paste.